Menyiapkan Lulusan Pesantren yang Adaptif Digital: Workshop Fotografi dan Videografi Dasar di Magelang - Yusuf Wahyu Setiya Putra; Mira Fitriana (Lembaga Pengembangan Kinerja Dosen, 2026)
Abstract: The digital era demands that every individual possess visual literacy competencies, but in Islamic boarding schools (pesantren), access to technology is often limited to maintain focus on worship. The main problem at the Salafiyah Al-Furqon Islamic Boarding School in Sawangan, Magelang Regency, is the digital skills gap among 12th-grade students. This is caused by the boarding school's policy of only allowing mobile phone use during semester breaks, leaving students lacking practical multimedia skills prior to graduation. This community service activity aims to provide a solution through basic photography and videography training as a soft skill for alumni independence. The method used is a workshop that combines theoretical explanations and direct practice (experiential learning). The results of this activity show a significant increase in students' technical competency; participants are able to operate smartphone cameras with stable shooting techniques, understand the principles of visual composition (such as the rule of thirds and leading lines), and are able to perform basic video editing using mobile-based software applications. Through this training, Islamic boarding school graduates are expected to become individuals who are adaptive to technological developments and able to utilize visual media as a means of creative economics and digital da'wah after graduation.